Research on the formation process of selective laser melting Mg–Y–Sm–Zn–Zr alloy. Issue 2 (22nd January 2021) - Wang, Wenli; He, Lun; Yang, Xin; Wang, Dan
Abstract : Selective laser melting technology was proposed to form the multi-element mixed rare earth magnesium alloys of Mg–3.4Y–3.6Sm–2.6Zn–0.8Zr (wt-%). The formation process, relative density, evaporation, microstructure and microhardness of the deposited samples at different laser power and scanning speed were characterised. Under the experimental conditions with a laser power of 40 W and a scanning speed of 300 mm s −1, the maximum relative density of the sample is 98.6%. The evaporation of elements exists but is not serious under all process parameters. Compared with the as-cast process, the microstructure of the samples prepared by SLM is mainly composed of α-Mg matrix and (Mg, Zn)3 (Y, Sm) eutectic phase, Mg12 (Y, Sm)Zn eutectic phase and LPSO structure are not found.